ANALISIS DAMPAK LALU LINTAS AKIBAT AKTIFITAS PADA KAWASAN PASAR TURI BARU SURABAYA - Hapsari, Yunita Tri; Sholichin, Ibnu; Estikhamah, Fithri (AGREGAT, 2024)
The increase in road traffic has caused traffic jams in the market area of New Turi Surabaya. The traffic jams on this street were caused by visitors' exits to the Surabaya New Turi Market. In this study on traffic impact analysis was carried out to find out the performance of bridges, side obstacles, level of service in the area of New Turi Market Surabaya. This study uses the intersection method guided by the 2014 Indonesian Road Capacity Guidelines (PKJI) on Traffic Signalling Tool Abnormalities. (APILL). This research was conducted for a week in busy hours. From the results of the calculation of traffic performance, obtained the saturation degree (DJ) Highway Dupak by 0.91, Market Road Turi by 0,93, Tembaan Road by 0.89, Semarang Road by 0.091. Whereas for saturation degrees (dJ) with APILL in the conditions of existing Road Dupak By 0.93 and the average delay (T) = 36.96 seconds/skr, Market Street Turi was 0.92 and the mean delay(T) was 49.76 seconds/sk, Tembaan Street was 0.89 and the medium delay was (T)) = 40.34 seconds/kr, Semarang Street was (0.93 and average delays(T)) was (49.02 seconds/sek). The highest saturation degree (DJ) is 0.93 with the level of service (LOS) E, because the area belongs to the crowded and center of market activity and the density of traffic flows.